Corrosion of cast Stellite-3 analogue in simulated PWR conditions - Karimi, G.N.; Shipway, P.H.; Stewart, D.A.; Hussain, T. (Elsevier, 2018)
Wear resistant alloys are required for deployment of pressurised water reactor primary circuits and in this context, the corrosion behaviour of a cast cobalt-based alloy following exposure for 30 days in lithiated water at 300°C was investigated. Corrosion of the surface was observed, resulting in the formation of a ~100 nm thick chromium and silicon-rich oxide. Preferential corrosion of the matrix at its interface with just one of the carbide types was observed to a depth of ~1 μm; for the first time this was found not due to any inhomogeneity in the matrix but was instead an electrochemical effect.